Preparation and Characterization of Promoted Fe-V/SiO2 Nanocatalysts for Oxidation of Alcohols - Hamid Reza Rafiee; Mostafa Feyzi; Fatanh Jafari; Banafsheh Safari (Journal of Chemistry)
A series of SiO2 supported iron-vanadium catalysts were prepared using sol-gel and wetness impregnation methods. This research investigates the effects of V and Cu on the structure and morphology of Fe/SiO2 catalysts. The SiO2 supported catalyst with the highest specific surface area and pore volume was obtained when it is containing 40 wt.% Fe, 15 wt.% V, and 2 wt.% Cu. Characterization of prepared catalysts was carried out by powder X-ray diffraction (XRD), scanning electron microcopy (SEM), vibrating sample magnetometry (VSM), Fourier transform infrared (FT-IR) spectrometry, temperature program reduction (TPR), N2 physisorption, and thermal analysis methods such as thermal gravimetric analysis (TGA) and differential scanning calorimetry (DSC). The Fe-V/SiO2 catalyst promoted with 2 wt.% of Cu exhibited typical ferromagnetic behavior at room temperature with a saturation magnetization value of 11.44 emu/g. This character of catalyst indicated great potential for application in magnetic separation technologies. The prepared catalyst was found to act as an efficient recoverable nanocatalyst for oxidation reaction of alcohols to aldehydes and ketones in aqueous media under mild condition. Moreover, the catalyst was reused five times without significant degradation in catalytic activity and performance.